Hubungan Berat Badan Lahir Dengan Kejadian Stunting Pada Balita Usia 24-59 Bulan Di Kelurahan Seberang Padang Tahun 2024 - Nurhaida; saputri, melda; Maulana, Alfin (BPPM Politeknik 'Aisyiyah Sumatera Barat, 2024)
World prevalence data in 2022, 148.1 stunted children, Indonesia with a stunting incidence rate of 21.6%. The Padang City Health Office said that toddlers who experienced stunting in Seberang Padang Village were found in the initial survey of 20 toddlers. The purpose of this study is to determine the relationship between birth weight and stunting incidence in toddlers aged 24-59 months in Seberang Padang Village in 2024.This type of research is analytical with a cross-sectional approach design; this study was conducted on July 23 – August 03. The study population was mothers who had toddlers aged 24-59 months in Seberang Padang Village, a sample of 72 mothers who had toddlers was obtained. The sample use technique uses simple random sampling by distributing questionnaires to mothers of toddlers. The data analysis used was Univariate and Bivariate. The results of the research were obtained by children who had a normal birth weight (91.7%) and stunting incidence (86.1%). The results of the statistical test concluded that p=value =0.000 (p<0.05) which means that there is a significant meaningful relationship between birth weight and stunting incidence.